Tropical montane forest loss dominated by increased 1–10 hectare-sized patches - Xinyue He; Dominick V Spracklen; Joseph Holden; Zhenzhong Zeng (Environmental Research Letters)
Tropical forest loss continues across mountain regions at alarming rates, threatening biodiversity, carbon storage and ecosystem sustainability. To improve our understanding of the dynamics of tropical mountain forest loss, this study focuses on the trends in patch sizes of forest loss during the 21st century. The annual area of tropical mountain forest loss surged from 0.7 million hectares in 2001–2003 to >2.5 million hectares in 2019–2021. There was an increase across all categories in terms of the size of forest loss patches, but strikingly, more than half of this increase was attributed to the proliferation of intermediate-sized forest loss patches spanning 1–10 ha. Concurrently, there was a diminishing proportion of small-scale montane forest loss patches (<1 ha) across all tropical continents over time. Despite their reduced overall proportion, the annual area of small forest loss patches increased, primarily influenced by trends in the Asia-Pacific region. Our study provides up-to-date and spatially explicit information on the scale of tropical mountain forest loss, and temporal trends associated with these patterns, which is crucial for assessing the sustainability of mountain forest ecosystems, highlighting the need for targeted, region-specific strategies to slow or reverse forest loss.